Sehat Jiwa Cirebon: Intervensi Psikologi Positif Berbasis Kearifan Lokal Untuk Peningkatan Kesehatan Mental Masyarakat Pesisir - Habib Priyono; Annas Alkhowarizmi; Alvin Fachrully Septiano (STIKES Columbia Asia Medan, 2025)
Mental health among coastal communities remains a critical issue often overlooked by formal interventions. This community service activity aimed to enhance the psychological well-being of residents in Astapada Village, Gunungjati Subdistrict, Cirebon, using a positive psychology approach integrated with local cultural wisdom. The method used was a participatory community-based approach involving training in gratitude journaling, character strengths, and meaning therapy, combined with traditional arts practices such as mask dancing and batik making. Evaluation using the WHO-5 Wellbeing Index showed a significant increase in participants' psychological well-being scores, from an average of 43.77 to 66.40. Additionally, social initiatives emerged, including the formation of the “Rembug Jiwa” community and the rise of local leaders promoting program sustainability. These findings indicate that culturally contextualized positive psychology interventions can serve as effective strategies for improving mental health at the community level.